The Conditions and Challenges of Inclusive Education in Primary Schools - Nurhaswinda, Nurhaswinda; Jailani, Khairunnisakh; Slovenia, Salsa; Velonia, Dora Elfita; Jasmi, Elvi Syahri; Putri, Nadya Rewina; Putri, Kartika; Nikma, Hanati; Ningsih, Aulia; Fhahira, Sindy Viza; Rahman, Salsa Billah (The Future of Education Journal, 2025)
This study aims to describe the conditions and challenges in the implementation of inclusive education in elementary schools. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation in three inclusive elementary schools. The findings indicate that the implementation of inclusive education still faces various obstacles. As many as 80% of teachers admitted that they had not participated in inclusive education training in the past two years. Furthermore, 65% of students with special needs (SEN) experienced difficulties in basic skills such as reading and writing, while the remaining 35% encountered social and emotional barriers. On the parental side, 70% stated that they were helped by the existence of small group learning activities at school. Additionally, inclusive physical facilities were fully available in only one of the three schools, and the use of technology such as text-to-speech was implemented in only one school with limited frequency. Despite these challenges in infrastructure and human resources, social interactions between regular students and SEN students were relatively positive, with 85% of regular students showing cooperative attitudes toward their classmates with special needs. This study emphasizes the need for ongoing teacher training, provision of accessible facilities, and strong policy support and government oversight to realize fair and sustainable inclusive education.Keywords:  inclusive education, elementary school, students with special needs, support teachers, education policy.